Group-based guilt and reparation in the context of social change - Dumont, K.; Waldzus, S. (Journal of Applied Social Psychology, 2014)
This article examines how the consequences of group-based guilt depend on the perceptions of social change of the former perpetrator group. Informed by the Social Identity Theory and research on intergroup threat and help, the hypothesis was proposed that reparation intentions toward members of a victim group as the consequence of group-based guilt is moderated by the perceptions of changes of the status position of the in-group. Two correlational studies tested the assumption among whites in the context of post-apartheid South Africa. As predicted, the results of both studies show that the strength of the positive relationship between group-based guilt and reparation intentions decreases the more people perceive the loss of status for their in-group.